Relationship between innovation and sustainability in Latin American countries: Differences by perceptual characteristics of early-stage entrepreneurs - Gustavo Barrera Verdugo (Cogent Business & Management, 2020)
This research evaluates the relationship between innovation and sustainability in Latin American early-stage entrepreneurship. Besides, the study seeks to recognize differences in the relationship between innovation and sustainability by the perception of opportunities, the fear of failure, and companies' perceived social role, in early-stage entrepreneurs. Responses obtained in 11 Latin American countries are analyzed using correlation parameters and multinomial regressions. The results indicate a low association between innovation and sustainability in new businesses. Additionally, the findings demonstrate that entrepreneurs' perceptual conditions affect this connection. Notably, it is evidenced that entrepreneurs who perceive good opportunities, less afraid of failure, and identify an active social role of enterprises, tend to incorporate, jointly, higher innovation and sustainability in their new ventures. These outcomes extend the understanding about the effects of entrepreneurs' psychological characteristics on the development of innovation and sustainability in Latin American countries.
Keywords: 650; Business sustainability; product innovation; process innovation; perception of opportunities; fear of failure; social perception of enterprises; early-stage entrepreneurs